2021
DOI: 10.1002/hed.26779
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of primary radiotherapy with or without chemotherapy for advanced oral cavity squamous cell carcinoma: Systematic review

Abstract: Background Surgery with adjuvant radiotherapy is the accepted standard for treatment of advanced oral cavity squamous cell carcinoma (OCSCC); however, alternative evidence suggests that definitive (chemo)radiotherapy may have similar outcomes. Methods Systematic review was performed to assess the therapeutic value of radiotherapy or chemoradiotherapy as a primary modality for treating OCSCC. Meta‐analysis of outcomes was performed between articles comparing radiotherapy and primary surgical treatment. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Surgery or radiotherapy and chemotherapy cause great physical and mental damage to women. Thus, the timely screening of cervical precancerous lesions is key to the prevention and treatment of this disease and in improving the survival rate ( 11 ). Clinical studies have shown that it takes approximately 8–12 years for CIN to develop into invasive cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery or radiotherapy and chemotherapy cause great physical and mental damage to women. Thus, the timely screening of cervical precancerous lesions is key to the prevention and treatment of this disease and in improving the survival rate ( 11 ). Clinical studies have shown that it takes approximately 8–12 years for CIN to develop into invasive cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC), which is frequently encountered in the clinical setting, is the seventh leading cause of cancer-related death worldwide: approximately 700,000 new cases and 350,000 deaths were reported worldwide in 2018 ( Membreno et al, 2021 ; Sacco et al, 2021 ). HNSCC mainly includes cancers of the nasal cavity, paranasal sinus, oral cavity, pharynx, and throat, and over 90% of these cancers are squamous cell carcinomas ( Jing et al, 2021 ; Membreno et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC), which is frequently encountered in the clinical setting, is the seventh leading cause of cancer-related death worldwide: approximately 700,000 new cases and 350,000 deaths were reported worldwide in 2018 ( Membreno et al, 2021 ; Sacco et al, 2021 ). HNSCC mainly includes cancers of the nasal cavity, paranasal sinus, oral cavity, pharynx, and throat, and over 90% of these cancers are squamous cell carcinomas ( Jing et al, 2021 ; Membreno et al, 2021 ). Although there have been continuous advances in the field of comprehensive surgery, radiotherapy, and chemotherapy in recent years, the 5-year survival rate of HNSCC has not significantly improved, and 30–40% of patients are likely to develop distant metastasis within 5 years ( Membreno et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations